EXPERIENCED SITUATIONS TAKEN DURING THE STUDENT TEACHER TRAINING (Fiep Bulletin - online, 2011)
Concerning the relation between Teaching Practice and Student Teacher Training, Azevedo apud Piconez (1991) states that the theorie given in the beginning of the courses and the practice given by the end of them as supervised STT is the major evidence of the real distance from Theorie and Practice. Object this paper is to think over a blend of theorie and practice during tha supervised STT program and its contribution for the P.E. teachers education. Meant for the second part of elementary school ( 5TH to 9TH grade), the subject was taught at" Faculdade de Ciências e Tecnologia (FCT/Unesp)" that reached, through the STT , some public schools in São Paulo state and region. The thoughts made up upon the experiences taken in school helped to make some doubts clear up and also point out others related to the practical ask about theorie practice relation. This way the awareness process started with the reality revelation, in witch the proximity with school and its protagonists (administrators, teachers, students) was made possible. Going over the studied theorical references, concluding when observation and regency have really become dynamic in a way to allow, or at least to think about transforming the faced reality .It was spread to and discussed in the other subjects at the same time as in the STT subject, in the same semester.
Keywords: teacher's education; student teacher training program